An Open Educational Resource Supporting Mutation Testing Teaching - Paschoal, Leo Natan; Ruiz, João Pedro S. M.; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Mutation testing is widely recognized as one of the most effective criteria for software testing to uncover defects. However, there is an urgent need for more significant efforts to promote learning and understanding of this criterion. Currently, teaching support mechanisms in software testing tend to prioritize other criteria over mutation testing, exacerbating the gap. In this paper, we introduce MUT-STT, an open educational resource specifically designed to address this gap and facilitate the dissemination of critical concepts and practical aspects of mutation testing. MUT-STT focuses on the intrinsic concepts of the mutation testing criterion, providing comprehensive support for learners. It incorporates review exercises, offers tool suggestions for test automation, and provides clear instructions on applying the mutation test criterion using Python. An evaluation was conducted to ensure the educational resource’s content was complete and correct. In this evaluation, experts in mutation testing carefully examined MUT-STT, identifying and addressing any conceptual or descriptive defects that may have persisted.